2014
DOI: 10.1007/s12010-014-1257-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Cotton Coated With ZnO and ZnO-CNT Composites

Abstract: With the growing public health awareness of the pathogenic effects and strain formations caused by microorganisms, there is an increasing need for antibacterial materials in many applications. Zinc oxide (ZnO)-1,2,3,4-butanetetracarboxylic acid (BTCA) and ZnO-BTCA-carbon nanotube (CNT) composites were synthesized by simple stirring method. The synthesized materials were coated on cotton fabric by pad-dry-cure method separately. The coated fabrics were characterized by FT-IR analysis that revealed the cross-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The fabrics were tested against gram positive Staphylococcus aureus and gram negative Escherichia coli. They concluded that the ZnO-BTCA-CNT-coated fabric has very good antibacterial activity in compare with the ZnO-BTCA-coated fabric (Yazhini & Prabu, 2015).…”
Section: Application Of Cnt For Textile Wastewatersmentioning
confidence: 99%
“…The fabrics were tested against gram positive Staphylococcus aureus and gram negative Escherichia coli. They concluded that the ZnO-BTCA-CNT-coated fabric has very good antibacterial activity in compare with the ZnO-BTCA-coated fabric (Yazhini & Prabu, 2015).…”
Section: Application Of Cnt For Textile Wastewatersmentioning
confidence: 99%
“…In addition, CNTs have also been viewed as a potential nanofiller with an AF capacity (Beigbeder et al 2008;. Many studies have focused on the AF performance of CNTs on bacteria in laboratory bioassays (Kang et al 2007;Brady-Estévez et al 2008;Huggett et al 2009;Dong & Yang 2014;Yazhini & Prabu 2015). For example, Kang et al (2007) showed CNTs exhibited good efficacy for reducing the viability of Escherichia coli.…”
Section: Settlement Assaymentioning
confidence: 99%
“…Particularly, fabrics bearing antibacterial properties can offer synergistic and dual beneficial effects to the textiles. [40][41][42][43][44] Nanoparticles amalgamated with modified cotton fabrics, conferred an extensive antibacterial activity and well-balanced laundering durability. 45 This is principally mediated through the binding of MNPs into the surface of the fabrics by forming electrostatic forces or coordinating interactions between MNPs and co-ordinating groups.…”
Section: Introductionmentioning
confidence: 99%